Attitudes to dental hygienists: evaluation of the Dental Hygienist Beliefs Survey in a Swedish population of patients and students - KH Abrahamsson (Journal compilation 2007 Blackwell Munksgaard, 2007)
The aim was to evaluate and test the psychometric properties of the Dental Hygienist Beliefs Survey (DHBS) in a Swedish sample of different patient groups and students.